2019
DOI: 10.1155/2019/1520753
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Proteomics of the Fetal Pancreas Identifies Deficits in the Peroxisome in Rats with Intrauterine Growth Restriction

Abstract: Aim The objective of the present study was to identify differentially expressed proteins (DEPs) in the pancreas of a fetus with intrauterine growth restriction (IUGR) and to investigate the molecular mechanisms leading to adulthood diabetes in IUGR. Methods The IUGR rat model was induced by maternal protein malnutrition. The fetal pancreas was collected at embryonic day 20 (E20). Protein was extracted, pooled, and subjected to label-free quantitative proteomic analysis. Bioinformatics analysis (GO and IPA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As stated in previous studies, MS-based proteomics should strive to maintain accuracy within a range of 1.3- to 2-folds. Then, we chose the 1.5-fold change as an acceptable threshold of the statistically significant difference. …”
Section: Discussionmentioning
confidence: 99%
“…As stated in previous studies, MS-based proteomics should strive to maintain accuracy within a range of 1.3- to 2-folds. Then, we chose the 1.5-fold change as an acceptable threshold of the statistically significant difference. …”
Section: Discussionmentioning
confidence: 99%
“…IUGR increases the susceptibility to T2D and impairs glucose tolerance in adults [ 12 , 13 ]. We previously reported that maternal protein malnutrition leads to aberrant expression of Pex14 and FA metabolic enzymes in the fetal pancreas using an IUGR rat model [ 14 ]. Our knockdown assays using Pex14 siRNA support the hypothesis that downregulation of Pex14 lead to programed cell death and reduced resistance to lipotoxicity in the β cell.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that intrauterine growth restriction (IUGR) increases the susceptibility to adult T2D, owing to the maldevelopment of islets and β cell dysfunction [ 12 , 13 ]. In a previous study, we used a rat model to demonstrate the aberrant expression of pancreatic peroxisome factors in the IUGR fetus induced by malnutrition in utero [ 14 ]. Pex14, a peroxisome marker protein involved in the biogenesis and degradation of peroxisomes [ 15 ], was markedly reduced in the fetal pancreas that persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a complete loss of peroxisome function (through PEX14 silencing) has been shown to exacerbate lipotoxic phenotypes in response to palmitate treatment (Guan et al 2021 ), suggesting some level of peroxisomal β-oxidation is required to protect cells from the deleterious effects of accumulated VLCFAs, the most lipotoxic form of free fatty acids to β-cells (Plötz et al 2019 ). Furthermore, PEX14 protein expression is significantly downregulated in the foetal pancreas in a mouse model of intrauterine growth restriction, which predisposes animals to developing T2DM later in life (Liu et al 2019 ). Beyond β-oxidation, peroxisome-dependent synthesis of ether phospholipids has recently been demonstrated to support β-cell function under conditions where fatty acids are in excess.…”
Section: Unravelling the Mysteries Of Peroxisomes In Discrete Placesmentioning
confidence: 99%